1988
DOI: 10.1029/jb093ib06p06615
|View full text |Cite
|
Sign up to set email alerts
|

Calving icebergs: A source of low‐frequency seismic signals from Columbia Glacier, Alaska

Abstract: Low‐frequency icequakes produced by Columbia Glacier, Alaska, are caused by large icebergs which break off the glacier terminus into Prince William Sound. Occasionally, many ice seracs fall in rapid succession, producing complex, low‐frequency icequake signals with durations sometimes exceeding 10 min. An empirical relationship V = 4000 T between the volume V of an iceberg in cubic meters and the duration T of the seismic signal in seconds, can be used to estimate the calving rate of Columbia Glacier from seis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 16 publications
(4 reference statements)
11
80
1
3
Order By: Relevance
“…It is also possible that we observe parts of the acoustic signal of an event coupled with the ice surface in addition to direct seismic waves (Richardson et al, 2010 Two different general types of glacier-related seismic events close to the terminus, measured at local distances as in our study (i.e. several kilometers from terminus), have been consistently observed by several studies at the Columbia glacier, Alaska (Qamar, 1988;Walter et al, 2010) and on Greenland . Emergent, 2 s to several minutes long signals have been related to directly observed iceberg calving.…”
Section: Seismic Signal Characteristicsmentioning
confidence: 58%
See 1 more Smart Citation
“…It is also possible that we observe parts of the acoustic signal of an event coupled with the ice surface in addition to direct seismic waves (Richardson et al, 2010 Two different general types of glacier-related seismic events close to the terminus, measured at local distances as in our study (i.e. several kilometers from terminus), have been consistently observed by several studies at the Columbia glacier, Alaska (Qamar, 1988;Walter et al, 2010) and on Greenland . Emergent, 2 s to several minutes long signals have been related to directly observed iceberg calving.…”
Section: Seismic Signal Characteristicsmentioning
confidence: 58%
“…Calving events are often described as emergent low-frequency narrow-band (1-3 Hz) seismic signals (Qamar, 1988;, and impulsive, high-frequency acoustic arrivals when measured close to the glacier front (Richardson et al, 2010). As sources, fluid-filled cracks and fracture processes before the calving or the detachment itself, followed by overturning and scraping of icebergs on the ocean seafloor (Amundson et al, 2008) have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Our limited dataset, along with the data of Qamar (1988) and Warren and others (1995), indicates that there is little or no correlation between semi-diurnal tidal fluctuations and calving. This seems surprising in view of the fact that semi-diurnal tidal variations are about 5 m, about one-fifth of the average height above buoyancy.…”
Section: 33tidal Forcingmentioning
confidence: 99%
“…Brown and others, 1982;Meier and Post, 1987;Van der Veen, 1996), with less attention given to seasonal changes (Sikonia, 1982;Vieli and others, 2002) and even less to individual calving events (e.g. Qamar, 1988;Warren and others,1995;Motyka,1997).…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies using sensors with limited frequency bands focused on high-frequency components (>1 Hz) of regional calving seismograms (e.g. Qamar, 1988). More recently, such high-frequency signals with narrowband character (1-5 Hz) have been associated with interactions between detaching icebergs and the sea surface ( Bartholomaus and others, 2012) as well as various englacial fracture mechanisms that are active during calving events (e.g.…”
Section: Introductionmentioning
confidence: 99%